2009
DOI: 10.4269/ajtmh.2009.80.882
|View full text |Cite
|
Sign up to set email alerts
|

Marked Increase in Child Survival after Four Years of Intensive Malaria Control

Abstract: In malaria-endemic countries in Africa, a large proportion of child deaths are directly or indirectly attributable to infection with Plasmodium falciparum. Four years after high coverage, multiple malaria control interventions were introduced on Bioko Island, Equatorial Guinea, changes in infection with malarial parasites, anemia, and fever history in children were estimated and assessed in relation to changes in all-cause under-5 mortality. There were reductions in prevalence of infection (odds ratio [OR] = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
165
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(171 citation statements)
references
References 24 publications
4
165
0
Order By: Relevance
“…The Bioko respondents were also younger, had a higher educational level, and acceptance of the BIMC Programme launched in 2004 and its rapid malaria prevalence reduction in the first two years [22], and it is consistent with observations in other endemic areas of Africa [23][24][25][26].…”
Section: Bioko Island and Mainland Region In 2001supporting
confidence: 68%
“…The Bioko respondents were also younger, had a higher educational level, and acceptance of the BIMC Programme launched in 2004 and its rapid malaria prevalence reduction in the first two years [22], and it is consistent with observations in other endemic areas of Africa [23][24][25][26].…”
Section: Bioko Island and Mainland Region In 2001supporting
confidence: 68%
“…Six of these studies reported the effect of integrated vector management (such as combined use of IRS and ITNs) or combined introduction of preventative and treatment methods (such as IRS and rapid diagnostic tests) in a way that it was not possible to attribute a proportion of the change to a single intervention. [24][25][26][27][28][29] Three studies did not measure human health outcomes. [30][31][32] Two studies did not measure a change caused by IRS but rather established a baseline prevalence rate 33 or a change over time after termination of IRS.…”
Section: Methodsmentioning
confidence: 99%
“…eradication | migration | network analysis | imported malaria | community detection S ignificant progress is being made in reducing the morbidity and mortality attributed to malaria globally (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), encouraging the Global Malaria Action Plan (GMAP) (11) to articulate a long-term vision for malaria eradication through shorter-term local efforts to eliminate malaria. A total of 34 of the 107 malaria endemic countries have declared they have a national policy for malaria elimination or are pursuing spatially progressive elimination within their borders (11)(12)(13).…”
mentioning
confidence: 99%